'Nur'turing tumor T cell tolerance and exhaustion: novel function for Nuclear Receptor Nur77 in immunity. Issue 11 (25th October 2020) - Lith, Sanne C.; van Os, Bram W.; Seijkens, Tom T.P.; de Vries, Carlie J.M.
Abstract: The nuclear receptor Nur77 is expressed in a multitude of tissues, regulating cell differentiation and homeostasis. Dysregulation of Nur77 signaling is associated with cancer, cardiovascular disease, and disorders of the CNS. The role of Nur77 in T cells has been studied for almost 30 years now. There is a clear appreciation that Nur77 is crucial for apoptosis of self‐reactive T cells. However, the regulation and function of Nur77 in mature T cells remains largely unclear. In an exciting development, Nur77 has been recently demonstrated to impinge on cancer immunotherapy involving chimeric antigen receptor (CAR) T cells and tumor infiltrating lymphocytes (TILs). These studies indicated that Nur77 deficiency reduced T cell tolerance and exhaustion, thus raising the effectiveness of immune therapy in mice. Based on these novel insights, it may be proposed that regulation of Nur77 activity holds promise for innovative drug development in the field of cellular immunotherapy in cancer. In this review, we therefore summarize the role of Nur77 in T cell selection and maturation; and further develop the idea of targeting its activity in these cells as a potential strategy to augment current cancer immunotherapy treatments. Abstract : Nur77 expression and activation in T cells promotes tolerance and exhaustion. Tolerance comprises negative selection, suppression of self‐reactive T cells by Tregs, and T cells pushed into anergy. Exhaustion involves expression and activation of inhibitory receptors, such as PD‐1 and TIM‐3, resulting in lower effector cytokine release whilst promoting tumor growth.